Answer:
1.) f(x) = x*x - 7x + 10
2.) f(x) = x*x - 5x
3.) f(x) = 4*x*x - 5x - 6
4.) f(x) = 6*x*x -5x + 1
Step-by-step explanation:
1.) 2 and 5 (x -2)(x - 5) = f(x) = x*x - 7x + 10
2.) 0 and 5 f(x) = x*(x -5) = x*x - 5x
3.) -3/4 and 2 (x + 3/4)(x -2) = x*x - (5/4) x - 3/2,
need integers f(x) = 4xx - 5x - 6
4.) 1/2 and 1/3 (x - 1/2)(x - 1/3) = f(x)
x*x - 1/3 x - 1/2 x + 1/6
xx - 5/6 x + 1/6
6 xx - 5x + 1
Answer:100mm
Step-by-step explanation:
Answer:
Although the notation is sloppy, I will assume based on former questions of the same that "∑n=15[5(−2)^n−1]" translates mathematically to . Please correct me, though, if this in incorrect.
Anyway, there is neat formula that will deal with question very quickly. It is the following:
Sn is the sum of the geometric series
a1 is the first term in the series
r is the common ratio
n is the number of terms in the finite geometric series
Let's use this formula to our advantage! However, there are two variables that we do not know: a1 and n. Let's start with a1.The first term in the series is when n=1, so let's determine what that is.
Anwers:
1. line A
2. line D
3. line B
4. line C
Step-by-step explanation:
I think your question is missed of key information, allow me to add in and hope it will fit the original one.
Please have a look at the attached photo.
My answer:
Given the original function:
f(x) = 10x
and g(x) = a · 10x is the general from of all transformed functions from the above original function.
The graph of this function is stretched vertically => line A
The graph of this function is stretched vertically and is reflected through the x-asix => line D.
The graph of this function is compressed vertically => line B
The graph of this function is compressed vertically and is reflected through the x-asix => line C
Hope it will find you well.
Answer:
1/√5+√3= 1/√5+√3×√5-√3/√5-√3 = √5-√3/(√5)^2-(√3)^2 {(a+b)(a-b)= (a)^2-(b)^2} =√5-√3/5-3 =√5-√3/2 ans... Do you satisfied to my given answer
Step-by-step explanation: